Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Performing the body: performing the text - Jones, Amelia..; Stephenson, Andrew; Jones, Amelia; Stephenson, Andrew (Routledge, 1999)
This book explores the new performativity in art theory and practice, examining ways of rethinking interpretive processes in visual culture. Since the 1960s, visual art practices - from body art to minimalism - have taken contemporary art outside the museum and gallery; by embracing theatricality and performance and exploding the boundaries set by traditional art criticism. The contributors argue that interpretation needs to be recognised as much more dynamic and contingent. Offering its own performance script, and embracing both canonical fine artists such as Manet, De Kooning and Jasper Johns, and performance artists such as Vito Acconci and Gunter Brus, this book offers radical re-readings of art works and points confidently towards new models for understanding art.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; premier cycle; périodes historiques; thématiques

Strange sisters the art of lesbian pulp fiction, 1949-1969 - Zimet, Jaye (Viking Studio, 1999)
A vivid, sexy, and titillating journey into the steamy underworld of the dime novel. In the scandalous world of pulp fiction in the 1950s and into the 60s, detectives, gangsters, and mad doctors were joined on the racks by bad girls, dissolute youths, drug-crazed beatniks, and other assorted miscreants and misfits. Where romance met with soft porn there was also a surprisingly large population of butch brunettes pursuing and seducing blond femmes. This was an alternate universe of erotic pulp fiction where gals and dolls were exploring the illicit pleasures of lesbian love–much to the delight of a largely male, heterosexual readership. Before the sexual revolution of the 1960s, these books offered a thrilling peek into the deviant underworld of wild passion and scandalous sex. Strange Sisters is a collection of the cover art of these wildly wicked novels. The women who writhe across the covers of books such as Strange Lust ("She Wanted a Woman–Then She Met Another Woman Obsessed by the Same Burning Hunger") and Women's Barracks ("The Frank Autobiography of a French Girl Soldier") sizzle with sexual energy and freedom–in a high-camp defiance of the prudish, conservative 1950s. Bold, kitschy-colorful, and fraught with sexual tension, the covers of Strange Sisters are a siren call to the retro-groovin' man, or woman, in your life.
Keywords: 1900-1999; 1950-1959; 1960-1969; amériques; corps; fiction; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; régions géographiques; sexualité; thématiques; états-unis